e Model Sistem Rekomendasi Penentuan Jenis Tanaman Buah-buahan pada Lahan Pertanian Menggunakan Mikrokontroler Atmega 328p (Studi Kasus di Kabupaten Subang) - Wijaya, Anderias Eko; Sunendra, Ali (Puslitbang Kopertip Indonesia, 2019)
The land is a major factor in growing fruit for farmers. The selection of the right type of soil for planting fruit will affect the yield of the fruit. However, the problem at the moment is the lack of knowledge of farmers regarding the selection of suitable land. So often fruit harvest failures are caused by mistakes in the selection of fruit seeds planted on existing land. This system can answer the problems that occur in farmers who often experience crop failures due to errors in determining fruit planting. By utilizing Arduino Uno technology and by using two sensors in the form of pH meter sensors and Humidity sensors, a system will be formed that can be used as a fruit determinant based on pH indicators and temperature, the results of which refer to the results of data obtained from the Subang Regency Research Center.